Green Precursors and Soft Templating for Printing Porous Carbon-Based Micro-supercapacitors - Lochmann, Stefanie; Kintzel, Susann; Braeuniger, Yannik; Otto, Thomas; Zhang, En; Grothe, Julia; Kaskel, Stefan (Chemistry - A European Journal, 2021)
A combination of soft lithographic printing and soft templating has been used to fabricate high-resolution interdigitated micro-supercapacitors (MSC). Surfactant-assisted self-assembly produces high surface area ordered mesoporous carbons (490 m2 g−1). For the first time, such precursors have been printed by nano-imprint lithography as microdevices with a line width of only 250 nm and a spacing of only 1 μm. The devices are crack-free with low specific resistance (1.2×10−5 Ωm) and show good device capacitance up to 0.21 F cm−3.
CRIS-Team Scopus Importer:2022-04-14
Keywords: micro-supercapacitors; nanoimprint lithography; quasi-solid-state; soft lithography; soft templating